Weight reduction and pioglitazone ameliorate polycystic ovary syndrome after removal of a Sertoli-stromal cell tumor - Saito T; Ishioka S; Kiya T; Honnma H; Kuno Y; Morishita M; Shimizu A; Ikeda K; Endo T; Baba T (Dove Medical Press, 2012)
Tsuyoshi Baba,1 Toshiaki Endo,1 Keiko Ikeda,1 Ayumi Shimizu,1 Miyuki Morishita,1 Yoshika Kuno,1 Hiroyuki Honnma,2 Tamotsu Kiya,3 Shin-ichi Ishioka,1 Tsuyoshi Saito11Department of Obstetrics and Gynecology, Sapporo Medical University, Sapporo, 2Asada Ladies Clinic, Kasugai, Aichi, 3Ena Ladies Clinic, Ishikari, Hokkaido, JapanAbstract: This report presents an unusual case of Sertoli-stromal cell tumor and polycystic ovary syndrome successfully treated with weight reduction and an insulin-sensitizing agent. A 22-year-old woman, gravida 0, para 0, visited our hospital for the first time with a 12-year history of secondary amenorrhea and hypertrichosis. Transvaginal ultrasonography revealed a solid tumor in the right ovary. Right salpingo-oophorectomy was performed and pathological examination confirmed a Sertoli-stromal cell tumor. The patient's serum androgen levels declined postoperatively, but remained above normal. Pioglitazone treatment for 6 months also significantly reduced serum androgen levels, but they still remained above normal. However, after losing 12 kg of body weight, the patient's serum androgen levels declined to normal, and spontaneous menstruation became regular. Weight reduction with pioglitazone is an effective means of treating hyperandrogenism.Keywords: etiology, hyperandrogenism, pioglitazone, polycystic ovary syndrome, Sertoli-stromal cell tumor, weight reduction